THE CONNECTION BETWEEN DIGITAL MARKETING AND CUSTOMER RELATIONS FOR BUSINESS SUCCESS - Mshvidobadze, Tinatin (Social Economics, 2025)
in particular, the consequences of customer relationship orientation and the use of CRM technologies as a support for analysis, data integration and access to business performance. Customer Relationship Management (CRM) is becoming increasingly important for organizations as a prerequisite for the survival of the company. According to the study, CRM should be considered strategically for organizations. Therefore, this study focuses on the effects of digital marketing on business performance, in particular, the effects of customer relationship orientation and the use of CRM technologies as a means of supporting analysis, data integration and access to business performance. The study is based on quantitative methods to test hypotheses. Data was collected from various organizations. The results show the relationship between CRM and customer satisfaction, market performance and profitability. CRM technologies significantly improve business performance. This study contributes to existing knowledge by shedding light on the complex relationships between CRM, customer relationship orientation, market performance, market profitability and customer satisfaction. Based on the research results, we offer practical recommendations to managers and decision-makers. The relevance of the topic is determined by the fact that digital marketing is one of the fastest growing areas in the world. It is relevant in developed countries, both small and large companies find it very convenient to use digital marketing, as it significantly reduces costs and increases the level of communication with the consumer. As a result, we get a new economic model, which is the basis for the creation of a modern digital world.